2021
DOI: 10.2147/ijgm.s329911
|View full text |Cite
|
Sign up to set email alerts
|

Neutrophil Lymphocyte Ratio to Albumin Ratio and White Blood Cell to Hemoglobin Ratio as Prognostic Markers for Hepatocellular Carcinoma Patients Who Underwent Curative Hepatectomy

Abstract: Purpose Inflammation factors affect the prognosis of hepatocellular carcinoma (HCC). However, it is not clear if the preoperative neutrophil lymphocyte ratio to albumin ratio (NLRAR) and white blood cell to hemoglobin ratio (WHR) affect the prognosis of HCC post curative hepatectomy. We assessed the prognostic values of NLRAR and WHR in patients suffering from HCC who underwent curative resection. Materials and Methods A total of 169 eligible HCC cases were reviewed. Th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 29 publications
1
5
0
Order By: Relevance
“…WHR was a combined index of WBC and HGB and has been reported to be associated with the mortality in patients with gastric adenocarcinoma or hepatocellular carcinoma 10,11 . In this study, we found that high WHR was associated with high risk of 30 day mortality in HF patients admitted to the ICU.…”
Section: Discussionsupporting
confidence: 48%
See 2 more Smart Citations
“…WHR was a combined index of WBC and HGB and has been reported to be associated with the mortality in patients with gastric adenocarcinoma or hepatocellular carcinoma 10,11 . In this study, we found that high WHR was associated with high risk of 30 day mortality in HF patients admitted to the ICU.…”
Section: Discussionsupporting
confidence: 48%
“…WHR was a combined index of WBC and HGB and has been reported to be associated with the mortality in patients with gastric adenocarcinoma or hepatocellular carcinoma. 10,11 In this study, we found that high WHR was associated with high risk of 30 day mortality in HF patients admitted to the ICU. For HF patients, systemic inflammation was recognized as a common pathological and biological feature, which was linked to the disease progression and complication, and predicted the poor outcomes.…”
Section: Discussionmentioning
confidence: 60%
See 1 more Smart Citation
“…Many effector chemokines and cytokines have been described as being involved, resulting in an enhancement of tumor growth and invasiveness. Among its several physiological functions in the blood, serum albumin levels have been well-described as an inflammation marker and a prognostic marker in HCC [18][19][20][21][22][23][24][25][26][27][28][29][30][31] and albumin may actively participate in HCC growth control mechanisms [12,13,28,32], possibly through its ability to bind reactive oxygen species and so modulate inflammation [33,34].…”
Section: Discussionmentioning
confidence: 99%
“…[8,9] Recently it has been shown that preoperative white blood cells to hemoglobin ratio (WHR) are related to poor prognosis in patients with hepatocellular carcinoma after hepatectomy. [10] Meanwhile, preoperative fibrinogen to albumin ratio (FAR) has been shown to be associated with poor prognosis in a variety of cancers. [11][12][13][14] However, the effects of preoperative white blood cell to hemoglobin ratio (WHR) and fibrinogen to albumin ratio (FAR) on CRC patients have not been fully elucidated.…”
Section: The Authors Have No Conflicts Of Interest To Disclosementioning
confidence: 99%